MÁS ALLÁ DE LA FASCINACIÓN Y EL HORROR: HACIA UNA ESTÉTICA RELACIONAL DEL CINE CARIBEÑO (Revue D’études Interculturelles De L’image, 2018)
In this paper, I contend that the main tropes rehearsed by Édouard Glissant in his Poetics of Relation help us better understand the practices surrounding Caribbean filmmaking. Much of recent Caribbean filmmaking articulates experiences that reflect the need for a “relational” film aesthetics. These experiences fundamentally question the common understanding of “identity” as a timeless, fixed, territorial, and exclusionary, inherited from the colonial legacy and often perpetuated in mainstream film practices. Departing from Glissant’s notions of “relation” and “errancy,” I highlight the constraints of identitary demands contained in keywords such as ‘nation’, ‘race’, ‘gender’. This understanding informs my analyses of representative films by Félix de Rooy, Fernando Pérez, Fránces Negrón Muntaner and Luis Molina Casanova, in order to suggest that Caribbean film criticism better captures the region’s emancipatory potential in light of a relational film aesthetics.